1973
DOI: 10.1002/ps.2780040615
|View full text |Cite
|
Sign up to set email alerts
|

Diamphenethide—a new fasciolicide active against immature parasites

Abstract: Diamphenethide is the result of a search for a fasciolicide effective against immature parasites. The history of its development is followed from the active but toxic 4-tert-butoxyacetanilide (11) through the progressively more active and less toxic 4-allyloxyacetanilides to di-[2-(4-acetamidophenoxy)ethyl] ether, diamphenethide (vrr). Evidence is presented that the activity and good therapeutic index of VII depend on deacylation to (probably) the di-amino analogue (VIII) by liver deacylases, which occurs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Of those fasciolicides tested in this study, only diamphenethide showed no in vitro activity. This result was not unexpected because the activity of this compound against flukes in sheep has been ascribed to its free-amine metabolite (Harfenist, 1973). Clearly, the flukes themselves did not deacetylate this compound under in vitro conditions but it would appear that deacetylation did occur in the presence of rabbit liver homogenate or microsomes.…”
Section: Discussionmentioning
confidence: 86%
“…Of those fasciolicides tested in this study, only diamphenethide showed no in vitro activity. This result was not unexpected because the activity of this compound against flukes in sheep has been ascribed to its free-amine metabolite (Harfenist, 1973). Clearly, the flukes themselves did not deacetylate this compound under in vitro conditions but it would appear that deacetylation did occur in the presence of rabbit liver homogenate or microsomes.…”
Section: Discussionmentioning
confidence: 86%
“…The organic layer was dried over MgSO 4 , concentrated in vacuo with the residue, adsorbed onto silica (∼1.00 g), and purified by flash chromatography (2% CH 3 OH in CH 2 Cl 2 ) to afford the title compound (0.067 g, 65%) as a white solid (mp 158–164 °C). 46 …”
Section: Methodsmentioning
confidence: 99%
“…The reaction mixture was then stirred at room temperature for 16 h. The resulting reaction mixture was then concentrated in vacuo, diluted with ethyl acetate (100 mL), washed with water (2 × 100 mL), and saturated with NaHCO 3 (100 mL). The organic layer was dried over MgSO 4 , concentrated in vacuo with the residue, adsorbed onto silica (∼1.00 g), and purified by flash chromatography (2% CH 3 OH in CH 2 Cl 2 ) to afford the title compound (0.067 g, 65%) as a white solid (mp 158–164 °C) …”
Section: Methodsmentioning
confidence: 99%